2003
DOI: 10.1557/jmr.2003.0109
|View full text |Cite
|
Sign up to set email alerts
|

Highly localized acoustic emission monitoring of nanoscale indentation contacts

Abstract: This study evaluated a novel approach for acoustic emission (AE) monitoring of nanoindentation. The technique utilizes a miniature AE sensor integrated into a calibrated diamond indenter tip on a commercial nanoindentation system. The evaluation focused on the yield-point phenomenon in W (100); MgO (100); and sapphire C (0001); R (1012); A (1210); and M (1010) single-crystal surfaces. The minimum amount of elastic energy release sufficient to produce AE signal detectable with the indenter tip sensor was nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…An energy approach revealed by Dai et al (2002) and Mate (2007) can be used in quantifying 10 -12 -10 -15 J adhesive energy levels during close proximity between the head and media. This energy range matches well with the detectable equivalent AE energy levels correlated with elastic energy release during nanoindentation as measured by Daugela et al (2001) and Tymiak et al (2003). This fact suggests that a drive level ultra sensitive in situ AE monitoring technique is capable of capturing weak HDI interactions caused by degrading lubricant and particle induced slider and disc interference (e.g.…”
Section: Introductionsupporting
confidence: 87%
“…An energy approach revealed by Dai et al (2002) and Mate (2007) can be used in quantifying 10 -12 -10 -15 J adhesive energy levels during close proximity between the head and media. This energy range matches well with the detectable equivalent AE energy levels correlated with elastic energy release during nanoindentation as measured by Daugela et al (2001) and Tymiak et al (2003). This fact suggests that a drive level ultra sensitive in situ AE monitoring technique is capable of capturing weak HDI interactions caused by degrading lubricant and particle induced slider and disc interference (e.g.…”
Section: Introductionsupporting
confidence: 87%
“…Fortuitously, failure events in brittle materials are accompanied by abrupt changes in stress and strain fields, which lead to the generation of transient elastic waves in the form of acoustic emission. The real-time monitoring of acoustic emission can then be used as a qualitative and quantitative diagnostic tool [6][7][8]. This paper reports on the use of high resolution acoustic emission sensing to monitor nanoindentation induced fracture and characterize the initiation and progression of local failure processes.…”
Section: Introductionmentioning
confidence: 99%
“…This can be roughly compared to the high speed phenomena (<0.1 ls) such as plasticity yield point, materials phase transformation, and crystalographic orientation induced changes carried out by AE monitored nanoindentation process at the nanometer scale (Daugela et al 2001;Gerberich et al 2002;Tymiak et al 2003). In these experiments AE events were monitored at quasistatic loads of <100 lN.…”
Section: Physics Of Weak Hdi Interactionsmentioning
confidence: 96%
“…Here, the equivalent AE event energy can be obtained through the integration of elastic recovery represented by the loading segment of quasistatic force-displacement curve. Tymiak et al (2003) reported equivalent AE energy levels on the order of 10 -12 -10 -15 J. This fact suggests that a drive level ultra sensitive in-situ AE monitoring technique will be capable of capturing weak HDI interactions caused by degrading lubricant and particle induced slider and disc interference.…”
Section: Physics Of Weak Hdi Interactionsmentioning
confidence: 99%